Merupa Teater Kemuliaan Allah Sebagai Ruang Publik: Suatu Usaha untuk Mengonstruksi Suatu Ruang Publik Lewat Pemikiran John Calvin dan Ninian Smart di dalam konteks Agama-agama Dunia - Adrianus Yosia (Asosiasi Teolog Indonesia, 2018)
This article attempts to conceptualize the notion of ‘public sphere’ from the perspectives of Reformed theology and religious studies. This construction proceeds using a largely forgotten theological concept put forth by Calvin, namely the theater of God’s glory, in tandem with Ninian Smart’s phenomenological scaffold of the seven dimensions of religion. Through this constructive act, the author intends to demonstrate that Calvin’s concept of the theater of God’s glory can become a kind of ‘public sphere’ by means of an integration of thought with the aid of religious studies.